Digital literacy as framing: Suggestions for an interactive approach based on E. Goffmans frame theory - Manuela Pietraß (Universitetsforlaget, 2009)
Definitions of digital literacy in public discourse still focus mainly on technique, whereas educational studies want to break free from such functional concepts. To accomplish this, an approach is suggested that is not media-centred, but user-centred, which looks at the interaction that takes place on the internet. On the basis of Erving Goffmans frame theory, an example of such an approach is given.